Analisis Pengaruh Kompensasi Manajemen Terhadap Penghindaran Pajak (Efek Moderasi Kepemilikan Keluarga) - Amanta Anugrah Ilahi; Santi Yopie (Global Financial Accounting Journal, 2018)
This study intends to determine the relationship between management compensation variables have influence and family ownership as a moderating variable on tax avoidance with leverage, return on assets, firm size, company growth as a control variable. Populations in research are obtained from the Indonesia Stock Exchange. The total sample in the final observation that met the criteria was 847 company-years. Data collection methods use purposive samples. Use financial statement data and annual reports for all family companies. Data obtained were tested using panel regression. The results of this study stated that management compensation, family ownership, company size, leverage had no significant effect on tax avoidance. In contrast, this study found return on assets, the growth of the company has a significant influence on tax avoidance.